PWE-194 We've got to the caecum…now what will we do with the polyps?. (28th May 2012) - Bevan, R; Lee, T; Warren, M
Abstract : Introduction: Recent work, especially in the national Bowel Cancer Screening Programme (BCSP) has focussed on adenoma detection and removal as a marker of quality of colonoscopy. It is vital that this quality assurance is applied to all patients undergoing colonoscopy and that we move away from caecal intubation rate (CIR) as the main marker of a successful colonoscopy. We aimed to review practice in terms of adenoma detection and removal technique among all NHS colonoscopist in a busy district general hospital. Methods: Procedural data were retrospectively collected from Endosoft reporting software for all colonoscopies performed in a 6-month period. BSCP lists were excluded. The reports were reviewed and data collected including operator, size of list, extent of procedure, and details of polyps found—size, location, description, whether removed or biopsied, method of removal and if tattoo used. In addition, the completeness of the report was recorded. Where polyps were removed, the histology result was also recorded. Results: 472 procedures were performed by 18 operators—three trainees, two nurse endoscopists, and 13 consultants (eight gastroenterology, five surgical). 159 procedures identified polyps (246 polyps in total), with a unit polyp detection rate of 33.7%. Individual polyp detection rates varied between 14.7% and 58.8%. Histology showed a unit adenoma detection rate (ADR) of 21%. Eight cancers and one polyp cancer were detected. Documentation of polyp location was good (240/246) but size and description were less well documented (171 and 185 out of 246 respectively). 211 polyps were removed, 31 left in situ, and unclear in 4. 26 polyps removed were ≥10 mm, of which nine with a snare and 16 by EMR (one unknown.) Smaller polyps were removed by a variety of methods (Abstract PWE-194 table 1 ). Conclusion: ADR in this unit is comparable to elsewhere in the UK, but not as high as within the BCSP, although this represents a different patient population. Documentation of these polyps varied greatly, and could be improved. Detection rate and removal methods varied widely between endoscopists. This prompted the creation of an "aide memoir" poster (see Abstract PWE-194 figure 1 ) to be displayed in the endoscopy room, advising on documentation and highlighting the current guidance for management of polyps. Teaching was also undertaken at dedicated "polypectomy afternoons, " with a view to re-assessing polyp management at a later date, using ADR as quality marker. Competing interests: None declared.